2012
DOI: 10.1089/ars.2011.3967
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exercise Preserves Renal Structure and Hemodynamics in Spontaneously Hypertensive Rats

Abstract: Chronic ExT preserves renal hemodynamics and structure in SHR; these effects are partially mediated by improved redox status and decreased inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 60 publications
(64 reference statements)
8
64
0
1
Order By: Relevance
“…Indeed, differential expression of ACE and ACE2, Ang II and Ang (1-7), AT1, AT2 and Mas receptors, as well as differential responses to RAS stimulation were observed in vessels, kidney and plasma. 16,27,[34][35][36] One of the most important observations of the present study is that aerobic training promptly downregulates vasoconstrictor and vasodilator RAS axes in vessels of both normotensive and hypertensive animals, with a specific reduction of the vasoconstrictor axis in the renal artery of the SHR. The downregulation was an early response in both strains (significant changes were observed since the first week of training), being more pronounced in hypertensive individuals.…”
Section: Ras Hyperactivity In Hypertension 26-29supporting
confidence: 51%
“…Indeed, differential expression of ACE and ACE2, Ang II and Ang (1-7), AT1, AT2 and Mas receptors, as well as differential responses to RAS stimulation were observed in vessels, kidney and plasma. 16,27,[34][35][36] One of the most important observations of the present study is that aerobic training promptly downregulates vasoconstrictor and vasodilator RAS axes in vessels of both normotensive and hypertensive animals, with a specific reduction of the vasoconstrictor axis in the renal artery of the SHR. The downregulation was an early response in both strains (significant changes were observed since the first week of training), being more pronounced in hypertensive individuals.…”
Section: Ras Hyperactivity In Hypertension 26-29supporting
confidence: 51%
“…These findings indicate a dissociation of changes in blood pressure with changes in renal pathology in these KO mice. Such dissociation between the changes in renal perfusion pressure and in renal morphological injury was not at all unexpected as many previous studies have demonstrated that the reduction in blood pressure by hydralazine or hydrochlorothiazide failed to prevent ANG II-induced renal injury in many animal models of hypertension (1,15,25,36,37). It was also demonstrated that etanercept treatment can markedly reduce renal injury changes without affecting blood pressure in hypertensive rats induced by DOCA salt (11) or ANG II with high-salt intake (12).…”
Section: Discussionmentioning
confidence: 82%
“…However, it is noted that etanercept treatment caused minimal changes in blood pressure in both treated and untreated WT mice with a low dose of ANG II (10 ng/min). As endogenous TNF-␣ production is influenced by the status of oxidative stress (1,29,46,47), which is enhanced during NO deficiency (34), it is likely that the TNF-␣ activity would be greater in KO than in WT mice. Thus, it is expected that the effect of etanercept treatment would be more prominent in KO mice than in WT mice, as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced plasma albumin is an independent predictor of renal dysfunction [38] and exercise training (16 weeks at 60% of maximal aerobic velocity) has proven useful at reducing albuminuria (urinary albumin) in SHRs [39]. Nevertheless, a recent review notes a scarcity of data describing the effects of exercise training on plasma albumin in models of CKD [40].…”
Section: Ckd) Is Timelymentioning
confidence: 99%